Game RPG RALANTAS sebagai Media Pembelajaran Pengenalan Rambu Lalu Lintas untuk Siswa Sekolah Dasar - Bagus Arinto Purnomo; Sukirman Sukirman (Universitas Hamzanwadi, 2023)
Traffic signs are an important element to be known, especially by elementary school students. Lack of knowledge about traffic signs can lead to accidents while driving. The purpose of this research is to develop an RPG game for introducing traffic signs to elementary school students. The method used in this research is Research and Development with the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Testing conducted includes media testing and material testing using questionnaires for data collection. Data collection techniques involve questionnaires filled out by media and subject matter experts. Data analysis is performed using descriptive statistical analysis techniques. This study shows that the combination of an RPG game containing traffic sign introduction material can serve as a means to introduce traffic signs to students for better recognition. Based on student satisfaction questionnaire data, the System Usability Scale (SUS) score is 80, categorized as EXCELLENT, corresponding to a grade scale of B. It can be concluded that the Ralantas RPG game is highly suitable for use.